Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/avsc.12386
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the central Mediterranean xerothermic cliff vegetation

Abstract: Questions: What are the syntaxonomic and synchorological patterns of the xerothermic chasmophytic vegetation in the central part of the Mediterranean Basin? What are the diagnostic species of the high-rank syntaxa of Asplenietalia glandulosi, Onosmetalia frutescentis and Centaureo dalmaticae-Campanuletalia pyramidalis? Location: Mediterranean coastal and subcoastal areas of southern France, and of mainland Greece. Methods: The data set of 1,261 published relevés was analysed using hierarchical clustering (Flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Trinajsti c 1980Trinajsti c , 2008. However, Terzi et al (2018) showed floristic similarities with the associations of the Centaureo-Campanulion alliance, in the Northern Adriatic. These similarities are due to the occurrence of the halophytic taxa recorded in several other cliff associations of the Centaureo-Campanulion.…”
Section: Centaureetum Ragusinaementioning
confidence: 93%
See 4 more Smart Citations
“…Trinajsti c 1980Trinajsti c , 2008. However, Terzi et al (2018) showed floristic similarities with the associations of the Centaureo-Campanulion alliance, in the Northern Adriatic. These similarities are due to the occurrence of the halophytic taxa recorded in several other cliff associations of the Centaureo-Campanulion.…”
Section: Centaureetum Ragusinaementioning
confidence: 93%
“…Results were interpreted from a syntaxonomic standpoint on the basis of the occurrences of the association type-relev es within the clusters and the set of IndSp associated to each cluster. Diagnostic taxa of the higher syntaxonomic ranks (alliance, order and class) were deduced from the scientific literature (compare Terzi et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations